1999
DOI: 10.1046/j.1442-2026.1999.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of interhospital transport of patients with acute myocardial infarction

Abstract: Objectives: To describe the rate of complications in patients who undergo interhospital transport in the early stages of acute myocardial infarction and to determine whether instability in the emergency department is a predictor of these complications. Methods: A retrospective medical record review of patients with proven acute myocardial infarction transferred from Wyong Emergency Department to Gosford Hospital in the period 1994–96 was performed. Results: Three hundred and twenty‐three patients were transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…This might be a reflection of the patient population or stabilization of patients by the retrieval team prior to take‐off. Compared with a New South Wales study, 1 there was a higher rate of complications in AMI patients transferred (21% vs 1.2%). This might reflect the criteria used to assess complications in the patients in the present study.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…This might be a reflection of the patient population or stabilization of patients by the retrieval team prior to take‐off. Compared with a New South Wales study, 1 there was a higher rate of complications in AMI patients transferred (21% vs 1.2%). This might reflect the criteria used to assess complications in the patients in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…7 More recently and locally, a study of AMI patients again confirmed safety and concluded that medical escorts were probably unnecessary unless the patient was intubated or unstable (defined as ongoing pain, dysrhythmia, pump failure or symptomatic hypotension) prior to transport. 1 However, the study also noted that prior instability did not necessarily predict complications during transport.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations